THE EFFECT OF MECHANOACTIVATION AND MICROWAVE EFFECTS ON THE SURFACE PROPERTIES OF WATER AND AQUEOUS SOLUTIONS - S. D. Rudnev; A. I. Krikun; V. V. Feoktistova; V. V. Ivanov; M. V. Sumenkov (Новые технологии)
Most food mixtures, where the liquid acts as a dispersion medium, are formed with the participation of water and aqueous solutions,. The formation of stable surface interactions in disperse systems with the participation of water is based on overcoming the forces of surface tension at the interface between the phases. The aim of the research is to analyze the effect of mechanical activation during stirring and microwave exposure on the surface properties of water and aqueous solutions. The object of the research is distilled water, bottled “Berdovskaya taiga” drinking water, an aqueous solution of NaCl (3.33%), an aqueous solution of NaCl (3.33%) with the addition of 1% flour with stirring. The main research method is the method of capillary rise of liquid in a tube of small cross section, partially immersed in liquid. It has been established that both mechanical and electromagnetic effects change the surface energy of water and aqueous solutions. But their influence is ambiguous. Surface tension during mechanical activation by stirring decreases to a certain minimum for different time intervals for different solutions, and then increases to a certain level. The retention time of the reduced surface energy of distilled water after stirring at a frequency of 100 rpm is 60–80 s. There is a tendency for a noticeable effect of impurities on the surface tension. The more complex the solution and the higher the concentration of impurities, the lower its surface energy. According to the results of the research, for technological purposes, for example, dough kneading, it is recommended to mechanically process (mix) solutions for dough kneading for 60–70 s or microwave treatment for no more than 20 s.